2018
DOI: 10.1051/matecconf/201817204005
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment on Additive Manufacturing Technique to Fabricate Integral PEM Fuel Cell/Electrolyser Component

Abstract: Additive Manufacturing (AM) is a reliable technique to build multifunctional components with any complex geometry. The present paper assesses the role of two vital AM techniques, namely Selective Laser Sintering (SLS) and Selective Laser Melting (SLM) in the fabrication of integral Polymer Electrolyte Membrane (PEM) fuel cell/electrolyser component. Thus, the paper integrates the state-of-the-art technologies, namely additive manufacturing and fuel cell/electrolyser engineering. The US department of energy (US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Nowadays, additive manufacturing is the most powerful technique for fabricating porous material with complex internal and overall designs having enhanced properties compared to the other fabrication methods. The Additive manufacturing technique is well known for its versatility and accuracy [ 43 ]. 3D printing is not just restricted to the porous material.…”
Section: Fabrication Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, additive manufacturing is the most powerful technique for fabricating porous material with complex internal and overall designs having enhanced properties compared to the other fabrication methods. The Additive manufacturing technique is well known for its versatility and accuracy [ 43 ]. 3D printing is not just restricted to the porous material.…”
Section: Fabrication Technologiesmentioning
confidence: 99%
“…In this method, the pore agent is extracted by melting in the sintering process rather than decomposition and dissolving. The whole process is the same as the thermal decomposition, as shown in Figure 10 b, except for removing the pore agent by melting during the sintering process [ 18 , 43 ]. The two studies of Mg and ice as pore agents are shown in Table 8 .…”
Section: Fabrication Technologiesmentioning
confidence: 99%
See 1 more Smart Citation